Diffusion imaging of the human brain: a new pulse sequence application for a 1.5-T standard MR system. - Harada, K; Fujita, N; Sakurai, K; Akai, Y; Fujii, K; Kozuka, T (American Journal of Neuroradiology, 1991)
We developed a new pulse sequence and investigated whether the anisotropic diffusion in the human brain can be detailed with a standard whole-body MR imager. Apparent diffusion coefficient maps were produced by the proposed sequence using a 1.5-T MR unit. The sequence employed simultaneous application of three orthogonal gradients to achieve an optimal signal attenuation for imaging the brain without any increase in echo time. The orientation of the effective diffusion-encoding gradient was off-axis. On the in vivo apparent diffusion coefficient maps of four healthy volunteers, white matter tracts (the internal capsule and the corpus callosum) and the cortical and deep white matter showed anisotropic diffusion. In the gray matter, such as basal ganglia and thalami, anisotropic diffusion was not observed. A typical whole-body imager can provide in vivo human brain diffusion images of clinical quality. This technique has promising implications for the evaluation of brain development and the diagnosis of degenerative diseases.